Protamine-adsorbed magnetic nanoparticles for efficient isolation and concentration of hepatitis-C virus from human plasma samples - Yassin, A.; Elwaseef, A.; Elnashar, Magdy; Oldenburg, J.; Mayer, G.; Pötzsch, B.; Müller, J. (Royal Society of Chemistry, 2014)
Protamine hydrochloride adsorbed onto citrated superparamagnetic iron oxide nanoparticles represents an efficient tool for capturing and concentration of hepatitis-C virus from plasma samples, improving the sensitivity of downstream analysis by nucleic acid testing. © The Royal Society of Chemistry 2014.